Of Genius and Epiphany: Schlafes Bruder, Das Parfum, and Babette's Feast - Nicholas Vazsonyi (Studies in 20th & 21st Century Literature, 1999)
At first sight, all three works under consideration—Schlafes Bruder (1992), Das Parfum (1985), and Babette's Feast (1950)—appear to conform to "postmodern" conventions, such as a rejection of logocentrism or a playful borrowing of pre-existing literary motifs and styles. However, all three works also revive the category of "natural genius," despite the twentieth-century rejection of romantic idealism in matters of aesthetics. Moreover, these "geniuses" create "masterpieces," which invariably trigger epiphanous moments for the untrained and unsuspecting audiences to whom they are presented. This is true even for the otherwise parody- and pastiche-filled Perfume, where the phenomenon of genius and the irresistible effect of a "masterpiece" is treated seriously nonetheless. The article compares these three texts, revealing surprising correspondences in ideas, themes, and often even in the choice of words. It further ponders whether these authors have abandoned the post-Nietzschean relativization of "beauty" and "truth" by returning unreflectedly to a sentimental romanticism, or whether they suggest the transcendence of postmodernism.
Keywords: Schlafes Bruder; Das Parfum; Babette& #x27; s Feast; postmodern; conventions; rejection of logocentrism; logocentrism; literary motifs; styles; natural genius; twentieth-century; romantic idealism; aesthetics; geniuses; create; masterpieces; epiphanous; parody; masterpiece; post-Nietzschean; beauty; truth; sentimental romanticism; postmodernism